2007
DOI: 10.1159/000120624
|View full text |Cite
|
Sign up to set email alerts
|

Association of MAO-A Variant with Complicated Grief in Major Depression

Abstract: Background/Aims: It has been suggested that monoamine oxidase A (MAO-A) activity is involved in the pathogenesis of major depression. Bereavement-related complicated grief significantly increases the risk of major depression and has been shown to be influenced by serotonergic tonus, possibly conferred by MAO-A activity. Complicated grief – whose inclusion in DSM-V as a separate mental disorder is under discussion – has been shown to be a distinct syndrome with symptoms not seen in depression. Therefore, in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 71 publications
1
12
0
Order By: Relevance
“…Research on MAOA activity outside the field of childhood maltreatment has shown some evidence suggestng that the high activity MAOA allele is a vulnerability factor. For example, depressed bereaved participants had more complicated grief symptoms with more MAOA activity than with less [65]. Meyer et al [66] demonstrated increased MAOA density among depressed individuals compared to healthy controls, suggesting that higher MAOA activity is related to depressive symptomatology among clinically depressed individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Research on MAOA activity outside the field of childhood maltreatment has shown some evidence suggestng that the high activity MAOA allele is a vulnerability factor. For example, depressed bereaved participants had more complicated grief symptoms with more MAOA activity than with less [65]. Meyer et al [66] demonstrated increased MAOA density among depressed individuals compared to healthy controls, suggesting that higher MAOA activity is related to depressive symptomatology among clinically depressed individuals.…”
Section: Discussionmentioning
confidence: 99%
“…higher activity alleles would confer increased risk for symptoms of MD whereas lower activity alleles have been associated with increased risk for symptoms of ASPD). Supporting this expectation, Kersting and colleagues found that the more active 4R allele of MAOA was significantly associated with complicated grief in female patients (Kersting et al, 2007). Similarly, Yu and co-workers found an increased frequency of the 4R allele among female MD patients as well as enhanced response to antidepressant treatment among 3R allele patients (Yu et al, 2005).…”
mentioning
confidence: 90%
“…They also found that the low activity variant of the 5HTTLPR (SS or SL genotypes) was associated with higher scores in depression, anxiety and somatic symptoms only among sexually abused adolescents with low MAOA-mVNTR activity alleles. Kersting et al 36 evaluated patients with major depression and a history of bereavement and they found that the longer allele of the MAOA-mVNTR was significantly associated with complicated grief in females.…”
Section: Major Depressive Disorder (Mdd)mentioning
confidence: 99%